- 783

- 1

This was on a test but I couldn't quite solve for x:

[tex]5^2^x + 4(5)^x = -3[/tex]

let [itex]5^x = y[/itex]

[tex]y^2 + 4y + 3 = 0[/tex]

[tex](y + 1)(y + 3) = 0[/tex]

So I end up with [itex]5^x = -1[/itex] or [itex]5^x = -3[/itex], but I don't think that makes sense... what am I doing wrong? It must be something dumb I'm doing :shy:

[tex]5^2^x + 4(5)^x = -3[/tex]

let [itex]5^x = y[/itex]

[tex]y^2 + 4y + 3 = 0[/tex]

[tex](y + 1)(y + 3) = 0[/tex]

So I end up with [itex]5^x = -1[/itex] or [itex]5^x = -3[/itex], but I don't think that makes sense... what am I doing wrong? It must be something dumb I'm doing :shy:

Last edited: